Thyroid Disorders-A common Cause of Infertility: A Review (Faridpur Medical College Journal, 2021)
Undiagnosed and untreated thyroid disease can be a cause for infertility as well as sub-fertility. Both these conditions have important medical, economical, and psychological implications in our society. Thyroid dysfunction can affect fertility in various ways resulting in anovulatory cycles, luteal phase defect, high prolactin (PRL) levels, and sex hormone imbalance. Thyroid hormones are instrumental in reproductive physiology. In hypothyroidism, there is decreased synthesis of factors VII, VIII, IX and XI and estrogen break through bleeding secondary to anovulation, which may explain the frequent, prolonged and heavy menstruation. Hyperthyroidism may be characterized by infrequent scanty menstuation or amenorrhea. Thyrotoxicosis increases the risk of spontaneous abortions and especially if on methimazole, there is an amplified risk of congenital anomalies and aplasia cutis. In males, thyrotoxicosis cause abnormal sperm motility, while hypothyroidism may result in abnormal sperm morphology and both may cause erectile abnormalities.Faridpur Med. Coll. J. 2020;15(2): 95-97